2013
DOI: 10.1111/sji.12116
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy Conferred by a Novel Recombinant Mycobacterium bovis Bacillus Calmette‐Guérin Strain Expressing Interleukin‐12p70 of Human Cytokine and Ag85A of Mycobacterium tuberculosis Fusion Protein

Abstract: Mycobacterium bovis bacillus Calmette-Gu erin (BCG) immunization provides protection against tuberculosis (TB) in infants, but the antituberculosis protective immunity wanes gradually after initial immunization and lasts less than 15 years. Therefore, more efficacious vaccines are urgently needed. In this study, we constructed a new tuberculosis vaccine of recombinant BCG strain (rBCG-IA), which could express IL-12p70 of human cytokine and Ag85A of M. tuberculosis fusion protein, and investigated its immunogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been reported, vaccination with rBCG over-expressing ESAT-6 could induce stronger IFN-g response than BCG, but exhibited no significant improvement in protective efficacy against M. tuberculosis infection over BCG vaccine 30 ; rBCG-IA was able to elicit stronger humoral and cellular immune responses, while similar protective efficacy with parental BCG was revealed. 31 In this study, the bacterial load in spleen and lung was significantly reduced by immunization of various rBCGs, but the protective degree of diverse rBCGs varied from their immune response. In the short term, significantly lower bacterial load in spleen than parental BCG was exhibited on rBCG-1173s, which indicated that these rBCGs could obviously decrease the infection of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 67%
“…It has been reported, vaccination with rBCG over-expressing ESAT-6 could induce stronger IFN-g response than BCG, but exhibited no significant improvement in protective efficacy against M. tuberculosis infection over BCG vaccine 30 ; rBCG-IA was able to elicit stronger humoral and cellular immune responses, while similar protective efficacy with parental BCG was revealed. 31 In this study, the bacterial load in spleen and lung was significantly reduced by immunization of various rBCGs, but the protective degree of diverse rBCGs varied from their immune response. In the short term, significantly lower bacterial load in spleen than parental BCG was exhibited on rBCG-1173s, which indicated that these rBCGs could obviously decrease the infection of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 67%
“…In another study, in which IL-12 was co-expressed with Ag85A in rBCG::IL-12-Ag85A, the recombinant strain also induced stronger T cell proliferation and IFN-γ responses than pBCG, rBCG::Ag85A or rBCG::IL-12 [ 62 ]. In this case, rBCG::IL-12-Ag85A induced similar levels of protection as pBCG against M. tuberculosis challenge, but curiously, rBCG::IL-12 and rBCG::Ag85A provided less protection than pBCG with respect to bacterial counts in the lungs and spleen.…”
Section: Recombinant Bcg Strains Producing Cytokinesmentioning
confidence: 99%